2011
DOI: 10.4103/0253-7613.77356
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sublingual, vaginal, and oral misoprostol in cervical ripening for first trimester abortion

Abstract: Objectives:To compare the effectiveness and tolerability of misoprostol as a cervical ripening agent in first trimester abortion through three different routes of administration before surgical evacuation (SE).Materials and Methods:It was a hospital based prospective randomized open labeled parallel study. A total of 150 randomly selected married women were divided in three groups for sublingual (S/L), vaginal and oral 400 μg of misoprostol single dose administration. The drug was administered 3-4 h before SE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Parveen et al concluded that sublingual misoprostol is an effective and favorable cervical ripening agent for first trimester abortion as compared to vaginal and oral dosage forms ( 17 ). Some limitations included in this research; Lack of willingness of patients to choose medical approach of treatment os it is very slow in comparison with the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Parveen et al concluded that sublingual misoprostol is an effective and favorable cervical ripening agent for first trimester abortion as compared to vaginal and oral dosage forms ( 17 ). Some limitations included in this research; Lack of willingness of patients to choose medical approach of treatment os it is very slow in comparison with the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the time that the misoprostol give the complete abortion, in our study, mean ± STD was 20.7 ± 28.2h which was very close to the systemic review conducted in 2017 by Wu et al [ 11 ] In 2011, a published study confirmed that the administration of misoprostol by the sublingual route is better than the oral and vaginal routes for cervical ripening. [ 12 ] The mean length of hospital stay for women who took misoprostol in our study was 3.0 ± 2.9h. A study compared between the oral and vaginal misoprostol regarding length of hospital stay and they found no statistical significant difference between two mean (hours).…”
Section: Discussionmentioning
confidence: 78%
“…Dorr et al [ 19 ] also reported that the proportion of women who experienced uterine tachysystole or chorioamnionitis did not significantly differ by route of administration. Perveen et al [ 20 ] compared oral, sublingual, and vaginal misoprostol for cervical ripening for first-trimester abortion. The sublingual group had significant cervical dilatation, and the side effects were less as compared to the vaginal and oral routes.…”
Section: Discussionmentioning
confidence: 99%